A DISCRETE PARTICLE SWARM ALGORITHM WITH SYMMETRY METHODS FOR DISCRETE OPTIMIZATION PROBLEMS - BAŞ, Emine; YILDIZDAN, Gülnur (Konya Journal of Engineering Sciences, 2023)
Particle Swarm Optimization (PSO) is a commonly used optimization to solve many problems. The PSO, which is developed for continuous optimization, is updated to solve discrete problems and Discrete PSO (DPSO) is obtained in this study. With DPSO, the Traveling Salesman Problem (TSP), which is well-known in the literature as a discrete problem, is solved. In order to improve the results, the swap method, the shift method, and the symmetry method are added to DPSO. The symmetry method is a new and successful method. The variations of the DPSO occurred according to the selected method type (DPSO1 (swap method), DPSO2 (shift method), DPSO3 (swap and shift methods), DPSO4 (symmetry method), DPSO5 (swap, shift, and symmetry methods), DPSO6 (swap, shift, symmetry, and 2-opt methods)). The effect of each method on the performance of the DPSO has been studied in detail. To demonstrate the success of the variations of the DPSO, the results are additionally compared with many well-known and new discrete algorithms in the literature. The results showed that the performance of DPSO has improved with the symmetry method and it has achieved better results than the discrete heuristic algorithms recently proposed in the literature. Parçacık Sürü Optimizasyonu (PSO), birçok problemi çözmek için yaygın olarak kullanılan bir optimizasyon yöntemidir. Bu çalışmada sürekli optimizasyon problemleri için geliştirilen PSO, ayrık optimizasyon problemleri çözmek için tekrar güncellenmiştir. Böylece Ayrık PSO (DPSO) elde edilmiştir. DPSO ile literatürde ayrık bir problem olarak bilinen Gezgin Satıcı Problemi (GSP) çözülmüştür. Sonuçları iyileştirmek için DPSO'ya takas yöntemi, kaydırma yöntemi ve simetri yöntemi eklenmiştir. Simetri yöntemi yeni ve başarılı bir yöntemdir. DPSO varyasyonları seçilen yöntem türüne (DPSO1 (takas yöntemi), DPSO2 (kaydırma yöntemi), DPSO3 (takas ve kaydırma yöntemi), DPSO4 (simetri yöntemi), DPSO5 (takas, kaydırma ve simetri yöntemleri), DPSO6 (takas, kaydırma, simetri ve 2 seçenekli yöntemler)). Her yöntemin DPSO'nun performansı üzerindeki etkisi ayrıntılı olarak incelenmiştir. DPSO'nun varyasyonlarının başarısını göstermek için, sonuçlar ayrıca literatürdeki birçok iyi bilinen ve yeni ayrık optimizasyon algoritmalarıyla karşılaştırılmıştır. Sonuçlar, simetri yöntemi ile DPSO'nun performansının arttığını ve literatürde son zamanlarda önerilen ayrık sezgisel algoritmalardan daha iyi sonuçlar elde ettiğini göstermiştir.